The taxation of foreign profits: The old view, the new view and a pragmatic view - Johannes Becker; Clemens Fuest (Intereconomics, 2011)
The increasing importance of multinational firms raises the question as to whether and how governments should tax repatriated profits, i.e. affiliate profits returned to the headquarters. The answer to this question is especially relevant for profit repatriations within the European Union where multinational firm investment is substantial and tax competition is supposed to be of rising intensity. This paper reviews the criticism of the standard view (the 'old view') of foreign profit taxation, which goes back to Peggy Musgrave. The 'new view' of international taxation is based on recent empirical studies and favours a system in which foreign profits are exempt from tax. The debate between old view and new view proponents is critically discussed and, finally, the two are confronted with a 'pragmatic view' on foreign profit taxation which crucially incorporates compliance and tax administration costs.
Keywords: 330